5-aminolevulinic acid in photodynamic therapy used in dermatology as a method of treating acne vulgaris. - Sacher, Karolina; Zabojska, Krystyna; Cygnarowicz, Aleksandra; Turemka, Mariola; Hosseinnejad, Negar; Wojtas, Aneta Klaudia; Biskupski, Mikołaj; Korotko, Urszula; Witowska, Kinga; Mandziuk, Aneta (Quality in Sport, 2025)
Acne therapy is a difficult task and the number of patients struggling with the disease is increasing, but new treatment options are emerging. One such indication is precisely the use of 5-aminolevulinic acid in photodynamic therapy for the treatment of acne lesions. The given issue has been widely discussed on the basis of a number of research papers from around the world, whose publications have promising results. The results of the studies show the effectiveness of using ALA-PTD terpy in the treatment of acne lesions occurring in acne vulgaris. Photodynamic therapy with 5-ALA acid may also serve as a good complementary treatment to other substances. However, studies need to be conducted to obtain data to develop procedures to achieve the most effective results, with the development of minimal side effects, which include pruritus, redness, transient hyperpigmentation coming off without leaving a scar and the occurrence of allergic reactions